Pengembangan E-Book Interaktif Musik Patrol untuk Meningkatkan Keterampilan Bermain Ansambel Siswa SMP: Development of an Interactive E-Book for Patrol Music to Improve Junior High School Students' Ensemble Playing Skills - Agung Budhi Nugroho; I Nengah Mariasa; Retnayu Prasetyanti Sekti (ITScience (Information Technology and Science), 2025)
Music arts learning in junior high school plays an important role in developing students’ musical skills and social attitudes through ensemble activities. However, local culture–based ensemble learning, particularly patrol music, still faces limitations in the availability of structured, contextual, and easily accessible teaching materials. As a result, the practice process is suboptimal and does not fully support the gradual development of ensemble performance skills. This study employed a research and development (R&D) approach using the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. The research subjects were 155 ninth-grade students of SMP Negeri 2 Sedati. Data were collected through expert validation (material, language, and media), teacher and student response questionnaires, learning outcome tests (pretest and posttest), and observations of ensemble performance skills. Data were analyzed using descriptive quantitative techniques, including feasibility and practicality percentages and N-gain analysis. The interactive patrol music e-book was found to be very feasible, with validation scores of 92% from material experts, 92% from language experts, and 94% from media experts. The practicality of the e-book was rated very practical, as shown by teacher response scores of 96.25% and student response scores of 94.35%. The effectiveness of the e-book was demonstrated by an improvement in learning outcomes, with an N-gain value of 0.56 (moderate category), as well as the achievement of ensemble performance skills with an average score of 88.28%, categorized as very good. The developed interactive patrol music e-book has been proven feasible, practical, and effective as a music arts learning medium for improving junior high school students’ understanding and ensemble performance skills grounded in local culture.